Proces prywatyzacji Stoczni Szczecińskiej Nowa Sp. z o.o. w latach 2004–2009 - Kamola-Cieślik, Małgorzata (Przegląd Politologiczny, 2018)
Between 2004 and 2009, Stocznia Szczecińska Nowa Sp. z o.o. (SSN) was one of the largest state-owned Polish companies in the shipyard sector. The privatization of the shipyard was a pivotal element of the economic plans put forward by the Governments of Marek Belka, Kazimierz Marcinkiewicz, Jarosław Kaczyński and Donald Tusk. However, this postulate was not implemented by their respective Cabinets. The difficulties in privatizing the shipyard were due to a change in the policy towards the shipbuilding industry, delays in preparing economic plans which followed from the fact that the European Commission (EC) did not accept the restructuring plans made by the companies interested in taking over the property and the assets of the shipyard, and also because the authorities responsible for finding investors were incompetent in doing so. Marek Belka’s government plan to consolidate the shipbuilding industry, aimed at selling all the property and assets of SSN within the framework of the Corporation of Polish Shipyards, was rejected by the government of Marcinkiewicz. The guidelines for privatizing the shipbuilding industry promised by the Marcinkiewicz government were never formulated or defined for the sector. The program was later accepted by the Kaczyñski Government, which despite earlier promises failed to privatize the shipyard. Donald Tusk’s Cabinet was not able to live up to the challenges connected with the shipyard industry crisis. Negotiations between the Polish Government and Amber Sp. z o.o. over the privatization plan for the shipyard failed. The shipyard’s restructuring plan produced by Mostostal Chojnice SA was not accepted by the EC. The Tusk government failed to find an investor in the public tenders announced for the property and assets of the shipyard – a Qatar company withdrew its initial proposal to buy the shipyard and there were no other investors willing to take it over. This was the main reason for the ensuing bankruptcy of the Szczecin shipyard.